DETERMINANTS OF NEONATAL PAIN MANAGEMENT PRACTICES AMONG NURSES WORKING IN NEONATAL CARE UNITS IN WESTERN KENYA HOSPITALS - Ongori, Damaris; Okiri, Teresa (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Newborn babies in the neonatal intensive care units (NICU) and newborn units (NBUs) undergo various tissue-damaging procedures as a result of both diagnostic and therapeutic care. Each neonate may experience an average of 300 painful procedures throughout their period hospitalization surgeries inclusive. However, little is known about factors that determine the neonatal pain management practices among nurses working in NICUs in Kenya. Objective: To assess factors that determine neonatal pain management practices among nurses working in neonatal intensive care and newborn units. Methods: A descriptive analytical cross-sectional study design with qualitative and quantitative approach was used. The statistical package for social science version 22.0 software was used for analysis. Spearman’s tests assessed for associations and correlations. Confidence level was 95%. A p-value equal or less than 0.05 was considered significant. Results: Less than half of the respondents were aware of both the pharmacologic and non-pharmacologic methods used in management of pain in neonates. On beliefs and attitudes, less than half (42%) of the nurses believed that pharmacologic and non-pharmacologic interventions are vital in neonatal pain management. Only a third (33%) of the respondents felt that the pain assessment tool is accurate and effective. Use of pain assessment tools (5.6%), non-pharmacologic (34.8%) and pharmacologic (28.1%) pain intervention strategies was low. Majority used physiological and behavioral factors to assess pain in neonates. Knowledge of pharmacologic (p<0.0001) was significantly associated with the practice of pain management in neonates. Conclusion: The study highlights that pain management in neonates is influenced by a variety of determinants including participants knowledge on various pain management practices and attitude towards pain management in neonates. Knowledge of pharmacological pain interventions emerged as the main determinant of neonatal pain management practices among nurses. There is therefore need to enhance nurses’ knowledge on neonatal pain management aspects. This can be achieved through targeted trainings and CMEs on pain management in neonates.